Peran Pemuda Dalam Pilkada Serentak - Erisandi Arditama Arditama; Wenny Eka Septina (Jurnal Ilmu Politik dan Pemerintahan, 2019)
Urgent actions that need to examined agenda now is how to efforts to improve the community political participation, particularly relating to the role of civil society. Paradigm shift from state centered become society centered give a higher probability to the community to continue to and to develop the democracy in this country. As part of national components, youth cannot escape from political and evasive, for all people including the youth is zoon politicon or political creature. Youth becomes one of targets in goals in any election and general election. This is because the youth often still floating, so that it becomes rebutan for candidates and political parties who fought in elections / general election. Besides, focus examined in this post is the role of karangtaruna. Karangtaruna have strong relationships with youths, where are the early karangtaruna can be followed by a youth.The organization has any important to gain political participation of youth.